The effect of Sodium deoxycholate on the production of Newcastle virus inoculated in chorioallantoic membrane (Baghdad Science Journal, 2011)
Newcastle Disease is one of the most important disease world wide distributions which invade the flock in different age resulting in large economic losses. This study aimed to evaluate the effect of treatment with 4 different concentrations (0.25, 0.5, 1.0 and 2.0 %) of Sodium deoxycholate (SDC) on the vaccinal virus (La Sota) using inoculation in the fragments of Chorioallantoic membrane. The treatment with each of the above 4 concentrations of SDC resulted in an increase in the Hemagglutination titer (HA) of the virus (28, 29.6, 211.6, 214.6) respectively as compared to the HA titer value for the untreated virus (26.6). No significant differences were noticed among all concentrations with regard to their effect on the HA titer, except the concentrations of 1.0 and 2.0 % where significant differences were recorded (P > 0.05). The results of this study suggest that SDC has an important activity in enhancement of the replication of NDV through increasing the Hemagglutination titer, which has a great importance in vaccine production.